Compact Fractional Fourier Domains - Serbes, Ahmet (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2017)
In this letter, a method for finding the compact fractional Fourier domains is presented. As a measure of compactness, we take the l(1)-norm. It is proposed that there exists at least one fractional Fourier domain in which l(1)-norm of the transformed signal is minimum. A coarse-to-fine grid search strategy is adopted to find the optimum fractional Fourier transform angle thatmakes l(1)-norm minimum with low computational cost. Extensive simulation results validate the proposed method.
Keywords: Coarse-to-fine search; compact fractional Fourier domains; fractional Fourier transform; minimum l1 norm; TRANSFORM; Engineering